Linking LOPA and value engineering. Issue 2 (24th April 2013) - Norton, Kristin D.; Surmeli, Senem; Maher, Steven T.
<x xml:space="preserve">Abstract</x> While safety instrumented systems (SISs) can be an essential element of process facility design to minimize the potential for process incidents, in some cases they can also be over‐applied in the design phases of capital projects where the safety instrumented functions (SIFs) associated with the SIS are defined before the process hazards have been fully characterized. This approach may provide one mechanism for achieving a robust process control system design; however, the application of SIS also brings increased costs associated not only with the robust equipment needed to meet safety integrity level (SIL) requirements but also with the ongoing maintenance, testing, and procedures required throughout the SIS lifecycle. In order to balance the important safety benefits associated with the SIS with the increased capital costs it is critical to have a specific and comprehensive basis for decision‐making. This article will illustrate the value engineering benefits of using the combined Hazard and Operability (HAZOP) Study and Layer of Protection Analysis (LOPA) methodology to comprehensively evaluate a design and provide a decision‐making platform for determining whether protection for process hazards should be implemented using a SIF, a basic process control system (BPCS) feature, or alternate safeguard categories (e.g., relief valves, alarms, etc.) to ensure an adequate level of reliability without compromising safety. When the HAZOP/LOPA Study is performed following the value engineering session, the HAZOP/LOPA Study provides a critical cross‐check to ensure safeguards are adequate and that changes made during the value engineering study do not introduce additional hazards. In contrast, when the HAZOP/LOPA Study is performed prior to the value engineering session, it provides a basis for decision making to remove SIFs or switch the function to the BPCS when the risk was determined to be low by the team (as defined by specific operating company criteria). © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013